Analysis of a survey on young doctors' willingness to work in rural Hungary - Szócska Miklós; Eke Edit; Girasek Edmond (BMC, 2010)
Abstract Background The severe shortage of qualified healthcare staff in Hungary cannot be quickly or easily overcome. There is not only a lack of human resources for health, but significant inequalities are widespread, including in geographical distribution. This disparity results in severe problems regarding access to and performance of health care services. In this context, this report, based on research carried out in 2008, deals with a particularly relevant matter: the willingness of young doctors to work outside Budapest (the capital of Hungary). Methods We conducted a survey with voluntary questionnaires and focus group interviews at each of the four Hungarian medical schools, concerning career plans and related incentives among young medical doctors. In all, 524 residents responded to the question concerning their willingness to work in rural areas, and there were seven focus group interviews, with 3-7 participants in each group. The number of residents' places in Hungary were 832, 682, and 785 in 2006/2007, 2007/2008, and 2008/2009, respectively. Results The majority of those surveyed would like to work in Budapest or a large town. Fewer than 7% were willing to work in a town with less than 50 000 inhabitants. Most young doctors would like to work in a teaching hospital (i.e. an accredited training site for medical students and postgraduate trainees) or a major regional hospital. Conclusions The current system of medical training in Hungary tends to produce doctors who want to live in big cities and work in central hospitals. Rural regions and non-in-patient service alternatives seem either not to be targeted or seen as unattractive work places. More doctors would be willing to work in smaller towns and villages if in-hospital training was altered and if doctors were offered adequate incentives as part of a comprehensive human resource strategy (high salaries, high professional standards, good working environment, reasonable workload). If these changes do not occur, the existing geographical and structural imbalances will not be improved.